Exploring Ghanaian Female Entrepreneurs’ Well-Being and Related Business Outcomes - Hansen-Garshong, R. (University of Ghana, 2023)
Women engaged in entrepreneurship in recent times have been on the increase particularly within Africa. Ghana is one of the top three countries with the most women-led businesses in the world (Global Entrepreneurship Monitor, 2019). As the role of women entrepreneurs grow, the need to understand this group becomes ever more important. Understanding and promoting entrepreneurial well-being is not only crucial for the mental, emotional and physical health of individuals engaged in entrepreneurship, but it is also essential for enhancing business outcomes and sustaining entrepreneurship as a catalyst for economic growth. However, current studies on entrepreneurial well-being tend to focus more on quantifying well-being experiences and psychologizing well-being, with less attention paid to meanings and sense making of entrepreneurial well-being experiences within the Ghanaian context. A qualitative design was used to comprehensively explore the relationship between entrepreneurial well-being and business outcomes among 22 women entrepreneurs within the Ghanaian context. The Interpretative Phenomenological Analysis (IPA) was the chosen framework which guided the methodology, providing a nuanced exploration of the participants’ narratives and experiences. Through semi-structured individual interviews, participants shared their perspectives on the dimensions of well-being and the factors influencing well-being which contributed to the knowledge gap. The rigorous analysis of the collected data unveiled key themes, patterns, and connections within the participants' accounts. The study identified three ‘Group Experiential Themes’ (GET) from the data: (i) Holistic healthiness and financial adequacy; (ii) Person-centered and business-driven factors; (iii) Triadic-resource cycle. Each of the GETs is characterized by sub-themes reflecting some nuances in the data. The holistic healthiness and financial adequacy, further indicate that female entrepreneurs’ well-being encompasses sub-themes of psycho-emotional experiences which are characterized by points of divergence that reflect disruptions (stress, loneliness) and thriving (happiness, resilience), physical stability and fitness (access to health care) and body maintenance (grooming), and financial material obligations (taxes, expenditures) and material independence. Secondly, the theme on the person-centered and business-related factors identified some nuances within the sub-themes from the study on how intrapersonal factors such as grit, autonomy, and self-awareness influence well being; also indicates how (interpersonal) relationships such as social networks, and family dynamics are essential factors influencing well-being. Furthermore, business growth and business related determinants are also factors that influence their well-being. Finally, the study shows a triadic-resource cyclical relationship between well-being and business outcomes which highlighted proactive pathways of influence, including problem-solving, strategic thinking and decision-making, employee management, customer relationship management, and persistence, which in turn impact pivotal business outcomes such as product quality, employee well-being and development, customer satisfaction, business expansion and job creation, and training. These findings imply the need for relevant stakeholders’ attention to well-being issues, considering and putting psychological support systems such as entrepreneurial self-help and mentoring groups in place to improve their well-being and thus ensure better business outcomes.
PhD. Psychology
Keywords: Women; Africa; Ghana